PENJADWALAN PERAWATAN NITROGEN AIR COMPRESSOR MENGGUNAKAN METODE RELIABILITY AVAILABILITY DAN MAINTAINABILITY (RAM) - Dwiyanti, Puput; Lasalewo, Trifandi; Rasyid, Abdul (Universitas Bina Taruna Gorontalo, 2023)
This research aims to increase the reliability and availability of the Nitrogen Air Compressor machine and determine the maintenance schedule for the Nitrogen Air Compressor machine. The method used in this research is the Reliability Availability and Maintainability (RAM) method to determine the level of Reliability Availability and Maintainability on Nitrogen Air Compressor machines to determine more optimal maintenance scheduling. The results of this research showed 4 defects in the Nitrogen Air Compressor units C and D components, namely (1) Filter Dryer (M 580-1) (C) produced a system reliability value of 82.47%, a system maintainability value of 83.00%, and Availability that has been carried out can produce an inherent availability value of 99.67% and an operational availability value of 99.92%. (2) Air Inlet Filter (6.4198.1) (C) produces a system reliability value of 81.31%, a system maintainability value of 83.87%, and Availability that has been carried out can produce an inherent availability value of 99.92% and operational availability value is 99.92%. (3) Oil Filter (6.3464.1) (D) and produces a system reliability value of 81.34%, system maintainability value of 85.49%, and the Availability that has been carried out can produce an inherent availability value of 99.93% and operational availability value is 99.93%. (4) Filter Dryer (M 580-1) (D) produces a system reliability value of 80.%, system maintainability value of 85.49%, and Availability that has been carried out can produce an inherent availability value of 99.93% and an operational availability of 99.93%. From these results it can be concluded that the RAM method can determine more optimal machine maintenance scheduling. Suggestions for companies are that they can implement scheduling using the RAM method.